Electron microscopic observations of structures associated with the flagella of Spirillum volutans. - Swan, M A (1985)
Electron microscopy of thin-sectioned Spirillum volutans (ATCC 19554) showed that at the insertion site of the flagellum there was a cylindrical structure with a diameter of ca. 36 nm which extended ca. 19 nm into the cytoplasm. This structure, termed a cytoplasmic flagellar base, enclosed a central rod which was continuous with the hook. There was a continuation of the flagellar base into the peptidoglycan layer, enclosing ringlike structures and the central rod. The flagellar hook and proximal part of the flagellar filament contained a central channel which was large enough to accommodate the flagellin subunit. The flagella of fixed cells may project perpendicularly from the outer membrane in a position corresponding to a trailing, swimming orientation or may bend almost parallel to the membrane in a leading orientation. Maximum bending occurred in the hook region, which may be the structure responsible for executing changes in swimming direction.